ALBANIA’S RURAL SECTOR: ANALYSIS OF INSTITUTIONAL CHANGES, EVOLUTION, CHARACTERISTICS AND CHALLENGES - Bregasi, Magdalena (European Scientific Journal, ESJ, 2013)
This article resumes existing theories for institutional changes in order to develop and to design the evolution, characteristics, and challenges of Albania rural sector. The current figures notes that agriculture accounts: 17% of gross domestic product (GDP), economic growth for agriculture 8% while the average growth of the sector during the period 2005 – 2010 has been 4%. The rural families not continue to dominate the national economy. According Albanian CENSUS 2011, for the first time, the population living in urban areas, 53.5%, has exceeded the population living in rural areas, 46.5%. In spite of the fact that emigration and urbanization brought a structural shift away from agriculture and toward industry and service, Albanian rural sector is the most important alternative of work for rural population. This sector employs almost half of the labour force, but is dominated by small family farms and local producers with low incomes. Besides, 40% of agro-industrial enterprises are in food processing sector. Many problems of sector are evident: legal transformation, restructuration of agricultural production, new orientation of agricultural market, ownership and financial support. The objective of this article is to analyse the problems and the perspectives from transition period to integration's target in EU of Albanian rural sector in the focus of institutional changes. Besides significants transformations, the analyse show that evolution of rural institutional changes in Albania continue to be a complex process and with different characteristics in time. The article recommends institutional strengthens in order to opent new opportunities in rural areas respecting approaches of sustainable development, environment and standards imposed by the European Union (EU).